Surface Properties of MoN Coated Engine Piston Rings - Hazer, Hanbey (Carl Hanser Verlag, 2010)
This paper presents an experimental investigation of surface behaviours of compression ring coated with molybdenum nitride (MoN) of a diesel engine. In the experiments carried out, the ring surface of a four stroke diesel engine was coated with MoN - a ceramic material with a thickness of 2.0 +/- 0.3 mu m - using the arc PVD method. Initially, the test engine MoN coated ring was tested for a while with a load of 1/2. Then, the same engine without a MoN coating was tested under the same conditions. Analyses of microhardness and SEM were carried out in order to examine surface characteristics of ring. The results show less deformation and fewer scratches due to wear on the MoN coated ring as compared to the uncoated one. We conclude that coating the ring surface of internal combustion engines with MoN contributes to longer life for the ring, and thus the engine, by decreasing the mechanical wear caused by friction.
Oberflächeneigenschaften von mit MoN beschichteten motorkolbenringen
Keywords: Molybdenum Nitride Coatings; Arc-Pvd; Automotive Industry; Wear; Substrate; Friction